Enhanced electrocatalytic HER performance of non-noble metal nickel by introduction of divanadium trioxide. (10th October 2019) - Zhou, Peng; Lv, Xingshuai; Gao, Yugang; Cui, Zihao; Liu, Yuanyuan; Wang, Zeyan; Wang, Peng; Zheng, Zhaoke; Dai, Ying; Huang, Baibiao
Abstract: Water dissociation, hydrogen adsorption and hydrogen desorption are three important processes for the electrocatalytic hydrogen evolution reaction in alkaline solution. According to the previous report that V–O species can promote the dissociation of water in the oxygen evolution reaction (OER), we wondered if introduction of V–O species to hydrogen evolution reaction (HER) electrocatalyst could also enhance water dissociation, and consequently improve the HER performance. To check this assumption, novel Ni/V2 O3 composite was prepared. The obtained electrode exhibits excellent performance including much lower overpotential (44 mV at 10 mA cm −2 ) and Tafel slope value (38 mV dec −1 ) compared to pure Ni and V2 O3 electrodes. In addition, the performance of Ni/V2 O3 is comparable to commercial Pt/C electrode. V2 O3 was proved to increase the Electrochemical Active Surface Area (ECSA) of Ni/V2 O3, which is an important reason for the increased HER performance of Ni/V2 O3 . Besides that, according to the combined results of Temperature-Programed Reduction (TPR) measurement, CO2 Adsorption, Contact Angle test and Density Functional Theory (DFT) calculation, it is believed that introduction of V2 O3 can promote the process of water dissociation as expected, as well as the hydrogen adsorption-desorption, and bubble separation, all of which together improves the HER performance of non-noble metal Ni. Graphical abstract: Novel Ni/V2 O3 electrode was successfully synthesized by heating treatment of NiV-LDH precursor which exhibits excellent HER performances including much lower overpotential (44 mV at 10 mA cm −2 ) and Tafel slope value (38 mV dec −1 ) compared to pure Ni, V2 O3 and many other Ni based electrodes.Image 1 Highlights: The noble Ni/V2 O3 system was successfully synthesized by using NiV-LDH as precursor which shows superior HER performance. Introduction of V2 O3 to metal Ni can increase the ECSA of the electrode material. Introduction of V2 O3 to metal Ni can promote the process of water adsorption, dissociation and desorption of hydrogen. The Ni/V2 O3 system can accelerate the separation of bubbles and reduce Ohmic resistance.